2007
DOI: 10.1063/1.2767188
|View full text |Cite
|
Sign up to set email alerts
|

Double-peak switching current in soft ferroelectric lead zirconate titanate

Abstract: Switching current measurements have been carried out on a soft lead zirconate titanate ͑PXE52, donor doped, modified proprietary composition with the overall formula PbZr 0.415 Ti 0.585 O 3 ͒. The experiments showed a single switching current peak during the application of electric field to a nonpoled ͑virgin͒ sample. However, an unusual double peak for the switching current was observed upon reversing the electric field polarity. The pyrocurrent for a forward and reverse poled sample showed a related behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…In contrast, at 100 K, the reduction in the average polarization parallel to the switching field is accompanied by substantial build up in the P x and P y components showing polarization rotation to within a standard deviation (Figure A). A similar switching mechanism has been described in MD simulations of tetragonal PbTiO 3 in which the system switched via an intermediate orthorhombic phase and supports experimentally observed double current peaks in prepoled PZT identifying non‐180 ◦ switching . We note that for the low temperatures case the standard deviation in P x,y slightly increases during the switching event, which is indicative of bond softening and the remnants of the competing rotational mechanism.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, at 100 K, the reduction in the average polarization parallel to the switching field is accompanied by substantial build up in the P x and P y components showing polarization rotation to within a standard deviation (Figure A). A similar switching mechanism has been described in MD simulations of tetragonal PbTiO 3 in which the system switched via an intermediate orthorhombic phase and supports experimentally observed double current peaks in prepoled PZT identifying non‐180 ◦ switching . We note that for the low temperatures case the standard deviation in P x,y slightly increases during the switching event, which is indicative of bond softening and the remnants of the competing rotational mechanism.…”
Section: Discussionsupporting
confidence: 86%
“…A similar switching mechanism has been described in MD simulations of tetragonal PbTiO 3 in which the system switched via an intermediate orthorhombic phase 25 and supports experimentally observed double current peaks in prepoled PZT identifying non-180 • switching. 36 We note that for the low temperatures case the standard deviation in P x,y slightly increases during the switching event, which is indicative of bond softening 34 and the remnants of the competing rotational mechanism. At the higher temperature the system responded to the applied field by nucleation of small reversed domains that can switch rapidly.…”
Section: Switching Dynamicsmentioning
confidence: 75%
“…Although the nucleation-and-growth process for 180 • switching events is fairly well understood, little evidence for 90 • -switchingmediated domain reversal has been presented. It has been suggested that broadened (or double) current peaks during reverse switching of previously poled PbZr 0.415 Ti 0.585 O 3 ceramics could be the result of non-180 • domain switching due the residual stresses developed during forward poling 43 44,45 . Despite these observations, the mechanisms underlying such behaviour are not entirely clear 46 and no direct measurements and examples of 90 • -switching-mediated domain reversal have been reported in the literature.…”
mentioning
confidence: 99%
“…The strain tensors are the same on the two sides of a 180°domain wall, so that 180°domain wall movements generally contribute only to the electric loss. 19 The 90°domain walls refer to walls between variants which differ in both polarization vector and strain tensor. Both 180°and 90°domain walls generally form to reduce the effects of depolarization fields, whereas only 90°domain walls may minimize the elastic energy.…”
Section: B the Contribution Of Domain Wall To Loss Factormentioning
confidence: 99%
“…The developing of internal stress due to an electric field is observed experimentally two decades ago. 19,20 For PMN-38%PT with tetragonal perovskite structure, the relationship between the mechanical loss factor, electric loss factor and the poling field are shown in Figs. 7.…”
Section: B the Contribution Of Domain Wall To Loss Factormentioning
confidence: 99%